Leadership Vision and Adaptive Strategies in the Metal Cutting Tools Industry in the VUCA World: A Case Study of BOYATECH (Thailand) Company Limited - Panjalak , Somcharn; Kangsadanporn, Korn (Journal of Dhamma for Life, 2025)
The objective of this research included to study the impact on the metal cutting tools industry in the world during the VUCA era, and to study the vision of leaders in adapting to the changes in the metal cutting tools industry in the world during the VUCA era. This qualitative research used in-depth interviews and focus groups with key informants consisting of organizational leaders, and senior and middle-level executives of BOYATECH (Thailand) Co., Ltd., as well as corporate leaders in the metal cutting tools industry. The results of the study found that business adjustment included (1) increasing efficiency and quality in production; (2) competitiveness enhancement; (3) developing new products; (4) creating sustainability in operations; and (5) strengthening confidence and trust from customers. It was also found that the impacts that occurred if there is no adjustment included (1) declining in sales and market share; (2) loss of customers and trust; (3) financial problems; (4) loss of qualified personnel; and (5) inability to maintain competitiveness. In addition, it was found that the vision of leaders in adapting to the world during the VUCA era consisted of five visions, including (1) being an example in adapting; (2) nurturing people to adhere to the same vision; (3) daring to think and change the work process; (4) pushing everyone to be an expert in their work; (5) truly caring for organization workers. However, from the results of the research, it was found that the adjustment may have negative impacts on the industry, including (1) high investment costs in adjustment; (2) uncertainty of results; (3) changes in production processes; (4) difficulties in management; (5) resistance to change by employees; and (6) changes in organizational culture.